영농 규모별 총요소생산성 추이 분석 - 허용준 (한국농촌경제연구원, 2013)
This study measures agricultural total factor productivity (TFP) in Korea and its components such as technological and technical efficiency change by estimating a normal production function and a stochastic frontier production function. Panel data of farm size and type was used to estimate the production functions for the period of 2003~2011. As regards to the TFP analysis by farm size, the annual average growth rates of potential TFP and actual TFP have increased 1.34% and 1.16% respectively, while the growth rate after the 2000s has slowed down. Especially in the case of the farm size of more than 7 ha, the annual average growth rate of TFP is the highest. The TFP analysis by farm type shows that average annual growth rates of TFPs in the relatively highly capital-intensive farm types, such as for livestock, special crops, fruits, and flowers, are much higher than that of paddy rice, a land-intentive farm.
Keywords: 총요소생산성; 한국농업; 확률프론티어 생산함수; total factor productivity; Korean agriculture; stochastic frontier production function